System identification : tutorials presented at the 5th IFAC Symposium on Identification and System Parameter Estimation, F.R. Germany, September 1979 - Isermann, Rolf (IFAC proceedings series., 1981)
System Identification is a special section of the International Federation of Automatic Control (IFAC)-Journal Automatica that contains tutorial papers regarding the basic methods and procedures utilized for system identification. Topics include modeling and identification; step response and frequency response methods; correlation methods; least squares parameter estimation; and maximum likelihood and prediction error methods.